Understanding the Dynamics of Self-discrepancy Formation of Self-injurious Adolescents: A Case Study of Self-injury - Hadi, Muhammad Abdul; Wicaksono, Banyu (Psychological Research and Intervention, 2021)
How the self-discrepancy of self-injurious adolescents was formed is yet to be understood clearly. Several studies have clearly stated that self-discrepancy contributes to propel adolescents to injure themselves. This study attempted to understand the dynamics of self-discrepancy formation in the sample of late adolescents who self-injure. This study used a descriptive qualitative research method and case study approach to examine this phenomenon. Data were obtained from six participants, using an open-ended questionnaire, which asks about how self-discrepancy in the participants was formed. Data were analyzed using thematic analysis to identify themes and subthemes that indicate how self-discrepancy was formed. The result showed that ten significant themes emerge in the self-discrepancy formation of self-injurious adolescents. Two factors contribute to form self-discrepancy among adolescents who self-injure: external dan internal. These factors are achieved from the familial and social interaction that are perceived negatively by the participants. Based on the results of this study, self-discrepancies in adolescent self-injurers should be considered when intervening in self-injurious adolescents.